[The Spanish version of the Short Form 36 Health Survey: a decade of experience and new developments]. - Vilagut, G; Ferrer, M; Rajmil, L; Rebollo, P; Permanyer-Miralda, G; Quintana, J; Santed, R; Valderas, J; Ribera, A; Domingo-Salvany, A; Alonso, J (2005)
OBJECTIVE: The Short Form-36 Health Survey (SF-36) is one of the most widely used and evaluated generic health-related quality of life (HRQL) questionnaires. After almost a decade of use in Spain, the present article critically reviews the content and metric properties of the Spanish version, as well as its new developments. METHODS: A review of indexed articles that used the Spanish version of the SF-36 was performed in Medline (PubMed), the Spanish bibliographic databases IBECS and IME. Articles that provided information on the measurement model, reliability, validity, and responsiveness to change of the instrument were selected. RESULTS: Seventy-nine articles were found, of which 17 evaluated the metric characteristics of the questionnaire. The reliability of the SF-36 scales was higher than the suggested standard (Cronbach's alpha) of 0.7 in 96% of the evaluations. Grouped evaluations obtained by meta-analysis were higher than 0.7 in all cases. The SF-36 showed good discrimination among severity groups, moderate correlations with clinical indicators, and high correlations with other HRQL instruments. Moreover, questionnaire scores predicted mortality and were able to detect improvement due to therapeutic interventions such as coronary angioplasty, benign prostatic hyperplasia surgery, and non-invasive positive pressure home ventilation. The new developments (norm-based scoring, version 2, the SF-12 and SF-8) improved both the metric properties and interpretation of the questionnaire. CONCLUSIONS: The Spanish version of the SF-36 and its recently developed versions is a suitable instrument for use in medical research, as well as in clinical practice.